Award presentation in honor of George B. Cook - United States. Navy; Naval Air Engineering Center (U.S.) (1963)
Award presentation in honor of George B. Cook, the first chemist to join the Naval Aircraft factory in 1922. The individuals in the photograph are identified as follows (from left): Jack Smith (Laboratory Supervisor); Dr. G.K. Holmes (Division Superintendent); Mr. Cook; J. Hartley Bowen, Jr. (Technical Director, Aeronautical Materials Laboratory).
Keywords: Aerospace Research Laboratories (U.S.); Employees; Naval Air Engineering Center (U.S.)